Cytologic Manifestations of Vaginitis - Dr. Ayesha Farheen; Dr. Aisha Humera (Tropical Journal of Pathology and Microbiology, 2017)
Introduction: As the lower genital tract is directly exposed to the external environment, it is subjected to inflammation as well as infection, which may remain localized or may progress to other areas such as the endometrium, fallopian tubes, peritoneal cavity and, less likely, the ovaries. Vaginitis is a common health problem. The main aim of the present study is to recognize the cytological manifestations in vaginitis and to identify the possible causative agent. Materials and Methods: Cytologic evaluations of vaginal smear were made in 167 patients. Clinical details were obtained by examining the patients and relevant investigations were noted. With the consent of the patient posterior vaginal fornix was swabbed with cotton tipped applicator. PH was determined. Whiff’s amine test was done for presence of fishy amine odor. Wet mount preparation was immediately made and examined under microscope. Three smears were made, one each for Gram’s, Giemsa and papanicolaou. Result: Out of 167 cases, most common cytological diagnoses offered were Bacterial vaginosis (50.8%), Koilocytotic atypia (13.7%), Trichomonas vaginalis infestations (12.5%), and vaginal candidiasis (4.8%). Majority were in age group 21-30 years (49.59%). Conclusion: There were diverse cytologic manifestations in vaginitis and was useful in identifying the possible etiological factors. Hence the results obtained are useful in screening large population.